Extracellular matrix proteins in the regulation of thrombus formation. Issue 3 (May 2016) - Wang, Yiming; Gallant, Reid C.; Ni, Heyu
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: Exposure of subendothelial extracellular matrix (ECM) proteins to the circulation is the key event that initiates platelet accumulation and clot formation after vessel injury. Soluble ECM proteins are also essential for support and regulation of these events. This review discusses the current understanding of ECM proteins in thrombosis and hemostasis. Recent findings: Fibrinogen and von Willebrand factor (VWF) are considered essential for thrombosis and hemostasis. Interestingly, αIIbβ3 integrin-dependent thrombus formation persists in the absence of fibrinogen and VWF, suggesting that other αIIbβ3 ligand (s), likely ECM proteins, can still mediate thrombosis. Fibronectin increases in platelets of fibrinogen-deficient humans and mice. This ECM protein can rapidly deposit onto the injured vessel wall prior to platelet accumulation. By switching from the soluble to insoluble form, plasma fibronectin supports hemostasis and inhibits excessive thrombosis. Fibrin, fibronectin, VWF, vitronectin, neutrophil extracellular traps, and other ECM proteins in the blood clot form a de-facto ECM, which interacts with various types of blood cells to regulate the evolution and resolution of the clot. Summary: ECM proteins are intricately involved in major steps of thrombus formation. Further investigations of ECM proteins will reveal new therapeutic targets for treatment of thrombosis and bleeding disorders. Video abstract: http://links.lww.com/COH/A12